(untitled) (Innovative professional education, 2022)
The article suggests that formation of professional-terminological competenceof future professional junior bachelors in agricultural engineering is one of the most importantchallenges of contemporary educational science. The article defines main problems of formationof professional-terminological competence of future professional junior bachelors inagricultural engineering and outlines possible ways to solve these problems.